Neurologic symptoms and signs observed in critical COVID-19 patients may be precursors of existing cerebrovascular disease - YILMAZ, Ayşe; SOYLU, Veysel Garani; DEMİR, Ufuk; TAŞKIN, Öztürk; DOĞANAY, Zahide (Journal of Health Sciences and Medicine, 2022)
Introduction: Although COVID-19 disease often includes respiratory system findings, that affects the gastrointestinal system, circulatory system, coagulation system and neurological system. In this study, we identified the neurological signs and symptoms observed in critical COVID-19 patients. Material and Method: This retrospective study reviewed 595 COVID-19 patients admitted to our intensive care unit (ICU) between January to June 2020. Patients with neurologic symptoms that were divided into two groups were diagnosed neurological disease (group ND) and non-neurological disease (group non-ND). Clinical signs and symptoms, radiological findings, demographic data (age, gender, presence of comorbidities), white blood cell (WBC), lymphocyte, platelet, lactic acid, glucose, and D-dimer levels, length of hospitalization, requirement of mechanical ventilation, and mortality were recorded for each patient. Results: Neurologic symptoms were observed in 148 (24.8%) patients. Of these, 44 patients were diagnosed neurological disease and 104 patients were non- neurological disease. The prevalence of neurologic symptoms was significantly higher in group ND. The rate of acute ischemic cerebrovascular disease in 595 critical COVID-19 patients was 6.2%. Conclusion: Presence of cerebrovascular diseases should be suspected in COVID-19patients with paresis, altered consciousness, numbness, taste/smell disorders, and plegia. The rate of ischemic cerebrovascular disease was approximately seven times higher than the rate of hemorrhagic cerebrovascular disease in critically COVID-19 patients.
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi; Intensive care unit; neurology; COVID-19; acute ischemic stroke; 3. Good health